Nature and Human in Interaction Depicted in Frances Hodgson Burnett’s The Secret Garden: Historical and Biographical Approach Analysis - Endang Susmiati; Tirmidi Tirmidi (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2026)
This study examines the influence of historical and biographical contexts on the themes, episodes, and settings in Frances Hodgson Burnett’s novel The Secret Garden. The study aims to uncover the historical factors and the author’s personal experiences that underlie the novel’s composition, as well as their impact on the narrative structure of the story. This study employs a descriptive qualitative method with historical and biographical approaches in literary discourse analysis. Data were obtained from the novel The Secret Garden, articles, books, and various relevant supporting sources. The data were analysed using the story grammar model proposed by Renkema. The results indicate that the novel’s central theme is individual transformation and healing through interaction with nature and the social environment. Historically, the novel reflects a shift in societal perspectives from the Victorian era toward the Edwardian era, which placed greater emphasis on children’s emotional and psychological needs. Biographically, Burnett’s personal experiences with loss, life’s hardships, and her passion for gardening also influenced the themes and symbolism of the secret garden in the novel. This study concludes that The Secret Garden serves as both a representation of the author’s personal experiences and a reflection of the socio-historical conditions of the early 20th century.